DNA-based taxonomy of a mangrove-associated community of fishes in Southeast Asia - Zainal Abidin, Danial Hariz; Mohd. Nor, Siti Azizah; Lavoué, Sébastien; A. Rahim, Masazurah; Jamaludin, Noorul Azliana; Mohammed Akib, Noor Adelyna (Scientific reports, 2021)
The Merbok Estuary comprises one of the largest remaining mangrove forests in Peninsular Malaysia. Its value is significant as it provides important services to local and global communities. It also offers a unique opportunity to study the structure and functioning of mangrove ecosystems. However, its biodiversity is still partially inventoried, limiting its research value. A recent checklist based on morphological examination, reported 138 fish species residing, frequenting or subject to entering the Merbok Estuary. In this work, we reassessed the fish diversity of the Merbok Estuary by DNA barcoding 350 specimens assignable to 134 species initially identified based on morphology. Our results consistently revealed the presence of 139 Molecular Operational Taxonomic Units (MOTUs). 123 of them are congruent with morphology-based species delimitation (one species = one MOTU). In two cases, two morphological species share the same MOTU (two species = one MOTU), while we unveiled cryptic diversity (i.e. COI-based genetic variability > 2%) within seven other species (one species = two MOTUs), calling for further taxonomic investigations. This study provides a comprehensive core-list of fish taxa in Merbok Estuary, demonstrating the advantages of combining morphological and molecular evidence to describe diverse but still poorly studied tropical fish communities. It also delivers a large DNA reference collection for brackish fishes occurring in this region which will facilitate further biodiversity-oriented research studies and management activities.